Pulse generation in 1.55 and 2.0 micron regions using passive saturable absorbers of bismuth telluride (Bi2Te3), nickel oxide (NiO) and spent coffee ground (SCG) materials / Muhammad Farid Mohd Rusdi - Muhammad Farid , Mohd Rusdi (2022)
In this research, three types of two-dimensional (2D) materials have been studied which are Bismuth (III) Telluride (Bi2Te3), Nickel oxide (NiO) and spent coffee ground (SCG). 2D materials are widely used in the application of optical communication, remote sensing and medical diagnostics. Sharing some advantages to photonic fields, the developed fiber laser is more robust, has zero alignments and has less operational technology. These materials have been prepared by mixing with the polyvinyl alcohol (PVA) solution to form a thin film saturable absorber (SA). These fabricated SAs are characterized in terms of nonlinear absorption parameters, linear absorption parameters, field emission scanning electron microscope (FESEM), electron dispersion spectroscopy (EDS), and Raman spectroscopy are being performed to confirm the presence of 2D materials in the fabricated SA. To validate the fabricated SA’s performance, the SA is integrated into the laser cavity by sandwiching a piece of SA in between two fiber ferrules. Two ring cavities were established using Erbium-doped fiber (EDF) and Thulium-doped fiber (TDF) as a gain medium as well to provide a sufficient nonlinearity in the cavity that operates at 1.55- and 2.0-micron regions, respectively. To avoid a selfpulsing instability, the free polarization isolator is used to suppress a multiwavelength and Brillouin backscattering. With EDF and TDF as the gain medium, the laser are successfully achieved with a stable Q-switched and mode-locked pulse for all materials. For example, NiO-based mode-locked Erbium-doped fiber laser (EDFL) and Thuliumdoped fiber laser (TDFL), the laser produces a stable pulse train at 1.89 MHz with a slope efficiency of 8.44% and pulse energy of 1.94 nJ at 51 mW pump power. In this study, we explore a new organic and waste material as SA, which is SCG. At a pump power of 56 mW, the stable mode-locked with a repetition rate of 1.81 MHz, slope efficiency of 9.18% and pulse energy of 2.76 nJ are obtained. These findings show that 2D materials especially organic materials have a great potential for photonics applications.